Tearing into the Web of Lies: Identity Narratives of Zitkala Sa - Pal, Virender (Integrated Journal for Research in Arts and Humanities, 2022)
Twentieth century has witnessed the development of native literature across the world. These literatures are an important endeavor on the part of natives to construct their identity. Constructed identity is important for them because the colonial narratives have maligned their identity and colonial policies have systematically obliterated their culture and history. The maligned identities and obliteration of culture have played havoc with the lives of the Natives. That is why the Native intellectuals are trying to redeem their identity and culture. They are writing narratives that are meant to transform the whites.